2020
DOI: 10.1177/1074248420967792
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis: Sex-Related Differences in ACE2 Activity May Contribute to Higher Mortality in Men Versus Women With COVID-19

Abstract: Angiotensin-converting enzyme 2 (ACE2) facilitates the cellular entry of the severe acute respiratory syndrome-associated coronavirus 2 (SARS-CoV-2), which causes the coronavirus-2019 (COVID-19) disease. Recent reports have shown worse outcomes in men with COVID-19 infection compared to women. We review the hypothesis that sex-related differences in outcomes in COVID-19 are due to different activity of ACE2 between men and women. We also show that studies in humans have demonstrated no significant difference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 24 publications
2
34
0
1
Order By: Relevance
“…Although recent evidence suggests that European women overall have slightly more comorbidities than European men [21], men are generally reported to have more life-threatening conditions, such as cardiovascular diseases, whereas women tend to have more non-fatal chronic diseases, such as migraine, musculoskeletal and autoimmune diseases as well as physical limitations [22][23][24][25]. Thus, the higher risk of death from COVID-19 among men may to some extent be explained by the relatively higher prevalence of underlying comorbidities such as cardiovascular disease, hypertension, diabetes and chronic lung disease [10,26,27]. Nevertheless, sex differences in health depend on the selected health dimension and the age group studied, and not all outcomes show differences between sexes or show very little differences [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Although recent evidence suggests that European women overall have slightly more comorbidities than European men [21], men are generally reported to have more life-threatening conditions, such as cardiovascular diseases, whereas women tend to have more non-fatal chronic diseases, such as migraine, musculoskeletal and autoimmune diseases as well as physical limitations [22][23][24][25]. Thus, the higher risk of death from COVID-19 among men may to some extent be explained by the relatively higher prevalence of underlying comorbidities such as cardiovascular disease, hypertension, diabetes and chronic lung disease [10,26,27]. Nevertheless, sex differences in health depend on the selected health dimension and the age group studied, and not all outcomes show differences between sexes or show very little differences [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 is cleaved from cells by metalloproteases such as ADAM10 and ADAM17 and is shed with an active catalytic site into plasma ( Turner, 2015 ), see Figure 3 ). Men appear to have higher plasma ACE2 levels than women (see Salah and Mehta, 2020 ). Physiologically, Ang-(1-7) has been shown to signal via a novel GPCR, Mas ( Bader et al, 2018 ).…”
Section: Mechanism For Sex Differences During Covid19mentioning
confidence: 99%
“…Part of the underlying reason for this is the effect of sex steroid hormones on RAAS, ( Dalpiaz et al, 2015 ; Turner, 2015 ; Melo Junior et al, 2020 ). Although it seems reasonable to anticipate sex-based differences and regulation of ACE2, research is limited, especially on human tissues ( Salah and Mehta, 2020 ; Samavati and Uhal, 2020 ; Song et al, 2020 ). With the COVID19 pandemic, attention has focused on ACE2 in the alveoli, but it has a wide tissue distribution.…”
Section: Mechanism For Sex Differences During Covid19mentioning
confidence: 99%
“…The ACE2 gene is located on the X chromosome and estrogens were shown to upregulate its expression ( 19 ), while TMPRSS2 was shown to be regulated by androgen receptor signalling ( 20 22 ). Preclinical studies of ACE2 tissue expression have shown different results depending on the tissue type ( 23 ): ACE2 expression seems to be higher in the lungs, heart or kidney of male ( 24 26 ), while pancreatic ACE2 expression seems to be higher in female ( 27 ). However, the relationship of tissue ACE2 expression and circulating ACE2 activity is still not well understood and data from the literature is partial contradictory ( 23 ): in human, the ACE2 activity was shown to be higher in healthy men and men with heart failure compared to matched women ( 28 , 29 ) while other studies showed no sex-related differences in serum ACE2 activity ( 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%